Prevalence, clinical investigation, and management of gallbladder disease in Rett syndrome. (15th February 2014) - Freilinger, Michael; Böhm, Michael; Lanator, Ines; Vergesslich‐Rothschild, Klara; Huber, Wolf‐Dietrich; Anderson, Alison; Wong, Kingsley; Baikie, Gordon; Ravikumara, Madhur; Downs, Jenny; Leonard, Helen
<x xml:space="preserve">Abstract</x> Aim This study determined the prevalence of cholelithiasis and/or cholecystectomy in Rett syndrome, described gallbladder function in a clinical cohort, and identified recommendations for assessment and management of gallbladder disease. Method The incidence of cholelithiasis/cholecystectomy was estimated from data describing 270 and 681 individuals with a pathogenic MECP2 mutation in the Australian Rett Syndrome Database and the International Rett Syndrome Phenotype Database respectively. Gallbladder function in 25 females (mean age 16y 5mo, SD 20y 7mo, range 3y 5mo–47y 10mo) with Rett syndrome (RTT) was evaluated with clinical assessment and ultrasound of the gallbladder. The Delphi technique was used to develop assessment and treatment recommendations. Results The incidence rate for cholelithiasis and/or cholecystectomy was 2.3 (95% confidence interval [CI] 1.1–4.2) and 1.8 (95% CI 1.0–3.0) per 1000 person‐years in the Australian and International Databases respectively. The mean contractility index of the gallbladder for the clinical sample was 46.5% (SD 38.3%), smaller than for healthy individuals but similar to children with Down syndrome, despite no clinical symptoms. After excluding gastroesophageal reflux, gallbladder disease should be considered as a cause of abdominal pain in RTT and cholecystectomy recommended if symptomatic. Interpretation Gallbladder disease is relatively common in RTT and should be considered in the differential diagnosis of abdominal pain in RTT.